2013
DOI: 10.1007/s00784-013-1068-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial to evaluate the impact of a dental care program in the quality of life of head and neck cancer patients

Abstract: Provision of continuous dental care for head and neck cancer patients can reduce deleterious side effects of the oncological treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…According to the literature, xerostomia is prevalent condition in patients with cancer, related to both the disease and the oncologic treatment, not presenting any significant impact by the dental care provided. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, xerostomia is prevalent condition in patients with cancer, related to both the disease and the oncologic treatment, not presenting any significant impact by the dental care provided. [ 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported inadequate compliance of a large number of patients because of death before the completion of study, refusal for a re-examination, withdrawal from the study, poor systemic health, administrative and technical difficulties [29]. Increased compliance might be achieved with the contribution of the appropriately educated dentist and the support and maintenance of oral health in head and neck cancer patients, as it was shown in the literature [33].…”
Section: Eortc Qlq Head/neck35mentioning
confidence: 92%
“…The head and neck region is a prevalent site for the occurrence of malignant neoplasms which mainly affect several oral tissues [1,2]. The treatment of cancer in the head and neck region is generally based on clinical staging, tumor location, histological differentiation, and the patient's clinical conditions [3,4]. Treatment is performed in most situations employing surgery or radiotherapy, and there may be cases that require both association therapy.…”
Section: Introductionmentioning
confidence: 99%